The Incidence Of Diarrhea In Toddlers In Terms Of Environmental Factors - Meiranti, Meiranti; Priyatno, Akhmad Dwi; Gustina, Erma; Yusnilasari, Yusnilasari (STIKes Al-Ma'arif Baturaja, 2025)
Tidal waters in the UPTD Puskesmas Muara Telang Banyuasin Regency cause river water to become salty during the dry season this is due to the habits of the community who defecate and throw garbage in the river. Data from the puskesmas for the months of January-June 2024 found 43 cases of toddlers who experienced diarrhea. This study aims to determine the results of the analysis of environmental factors on the incidence of diarrhea in toddlers in the working area of the Muara Telang Health Center, Banyuasin Regency in 2024. The method in this study was a quantitative observational survey analytic approach with a cross sectional design. Started on June 14, 2024-July 31, 2024. The population in this study were all mothers who brought toddlers to the health center, the sample in this study using the lemeshow formula obtained a sample of 60 toddlers. Accidental sampling technique. data analysis using univariate, bivariate and multivariate analysis. Instruments in the study Questionnaires and stationery. The results showed the incidence of diarrhea in toddlers as much as (58.3%). The results of bivariate analysis showed there was a relationship between age (p 0.016), gender (p 0.073), water quality (p 0.000), sewerage (p 0.044), and garbage disposal (p 0.025) with the incidence of diarrhea. The results of multivariate analysis of physical water quality variable is the factor that has the strongest relationship compared to other factors P value 0.000 (OlR 40.127). Further research is needed to fill the existing knowledge gaps related to the relationship between environmental factors and the incidence of diarrhea in toddlers.